Dispositions of Nostalgia - Nai, Sen Yang Israel (Curtin University, 2019)
This research aims to (1) conduct a systematic literature review (SLR) on the subject domain of nostalgia within the marketing/advertising context. Specifically, the review concentrates on published studies from 1979 to 2019, (2) conceptualise and operationalise a conceptual framework (nostalgia-disposition framework) for advertising practitioners through the understanding of three different consumer dispositions, and (3) investigate the moderating effects of brand-related variables such as brand heritage and brand attachment on the nostalgia-disposition framework across three furniture brands.